1991
DOI: 10.1002/hup.470060303
|View full text |Cite
|
Sign up to set email alerts
|

Performance tests in human psychopharmacology (3): Construct validity and test interpretation

Abstract: The content. criterion and face validity of human performance tests in psychopharmacology research were examined in an earlier paper. Most evidence on test meaning and interpretation, however, comprises construct validity. This is critically scrutinized here, through a brief analysis of human performance theory (Broadbent, Sanders, Sternberg), and taxonomies of human performance function (Fleishman, Holding). While much construct evidence is rather nebulous and untestable (non-disprovable), it is probably the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Subjects were required to substitute each digit with a different nonsense symbol, according to a key printed at the top of the sheet which indicated the nonsense symbol that corresponded to each digit. The test involves the recognition and recoding of sensory information and has been described as a measure of simple information processing 37 and of psychomotor performance. 38 It also assesses visuomotor coordination, sustained attention, and concentration skills.…”
Section: Compensatory Tracking Taskmentioning
confidence: 99%
“…Subjects were required to substitute each digit with a different nonsense symbol, according to a key printed at the top of the sheet which indicated the nonsense symbol that corresponded to each digit. The test involves the recognition and recoding of sensory information and has been described as a measure of simple information processing 37 and of psychomotor performance. 38 It also assesses visuomotor coordination, sustained attention, and concentration skills.…”
Section: Compensatory Tracking Taskmentioning
confidence: 99%
“…The reader is referred to reviews of antidepressant- [54], antipsychotic- [55,56], anxiolytic- [57], hypnotic- [58] and antihistamine effects on cognition and psychomotor performance [59]. The issues of psychometric assessment discussed in this article also apply in this area of research [46][47][48].…”
Section: Cognition Disease Targets For Drug Developmentmentioning
confidence: 97%
“…Parrott outlined the requirements for performance tests in human psychopharmacology: reliability and standardisation [46], content validity, criterion validity and face validity [47], construct validity and test implementation [48]. Sensitivity to psychoactive drug effect is also an important prerequisite for tests in this area, although traditionally it is not in itself considered as an index of validity.…”
Section: Scientific Implementation: Validity and Reliabilitymentioning
confidence: 99%
“…mianserin, trazodone) have been shown to cause more impairment than the newer antidepres sants (including lofepramine) in laboratory tests of cognitive and psychomotor function (Hindmarch et al, 1992). The older tricyclics have also been shown to cause impairment in driving tests, whereas SSRIs, reversible inhibitors of monoamine oxidase A (RIMAs) and nefazodone cause little or no impair ment (Louwerens et al, 1986;Raemaekers et al, 1994 Although these findings support the use of the newer drugs for long-term treatment, the predictive validity of psychomotor tests has been questioned (Parrott, 1987;Freeman & O'Hanlon, 1995).Many skilled tasks can be performed without undue effort and with spare processing capacity left available, and it has been suggested that information-processing tasks are measures of competence (potential) rather than actual performance (Parrott, 1991).…”
Section: Behavioural Effectsmentioning
confidence: 99%